Implementation of Early Mobilization to Overcome the Problem of Physical Mobility Disorders in Mothers After Caesarean Section at K.R.M.T Wongsonegoro Hospital, Semarang - Aditya Rizqi Surya Pratama; Witri Hastuti (Sean Institute, 2025)
Early mobilization is a critical postoperative intervention to accelerate recovery and prevent complications in mothers who undergo cesarean section. This study aims to describe the implementation of early mobilization and its effects on improving physical mobility among post– cesarean section patients at RSD K.R.M.T Wongsonegoro Semarang. Using a descriptive case study design, two patients who met the inclusion criteria were observed during the early postoperative phase. Data were obtained through direct observation and nursing documentation, focusing on mobility performance before and after the intervention. Early mobilization consisted of Range of Motion (ROM) exercises performed for 10–15 minutes over two consecutive days. The results showed that both patients experienced improvements in ease of movement and walking ability. The first patient, initially requiring total assistance, progressed to moving and ambulating with minimal assistance using supportive devices. The second patient, who initially demonstrated minimal mobility with dependency, improved to performing movements and walking with reduced assistance and without devices. These findings indicate that early mobilization effectively enhances muscle strength, blood circulation, and functional independence while reducing postoperative discomfort and fear of movement. Factors such as motivation, pain tolerance, and family support also influenced the level of progress achieved by each patient. Overall, early mobilization contributed positively to postoperative rehabilitation and supported a faster return to functional mobility. The study highlights the importance of integrating structured early mobilization into nursing care to optimize physical recovery and improve the overall quality of life for post–cesarean section mothers.